Evaluation of pH Dependent Solubility and Examination of Variation in Pharmacokinetic Properties of Alectinib: A Quantitative Study by Implementing Integrated Quality by Design Approach for RP-HPLC Method Development and Optimization - Kolasani, Durga Deepthi; Desai, Mrunal; Patil, Prajakta; Channabasavaiah, Jagadish Puralae (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Alectinib, an anaplastic lymphoma kinase inhibitor of BCS class IV, is said to have pH-dependent solubility and is susceptible to interactions with co-prescribed acid-reducing agents. Objectives: A micro-dissolution study was performed to determine the effect of modulations in gastrointestinal pH using biorelevant media and a sensitive RP-HPLC technique was developed for quantification of alectinib in the same using quality by design approach. Materials and Methods: Analytical method was developed and optimized in accordance with box-behnken design followed by micro-dissolution experiment mimicking physiological pH shift. Results: The solubility of alectinib in FaSSGF decreased from 0.648 μg/ml to 0.270 μg/ml whereas in FaSSIF it dropped down from 0.574 μg/ml to 0.108 μg/ml at the end of the micro-dissolution experiment. This reveals that elevation of pH from 1.2 to 6.8 has no significant impact on its solubility and hence will not influence drug absorption. Conclusion: Nonetheless, the study would be useful for therapeutic medication monitoring, dose adjustment of co-administered drugs, proactively driving clinical research design, and obtaining a readout on pH liability for high-risk anticancer medications.
Keywords: Alectinib; QbD; pH; ALK kinase; Micro dissolution